Interference-aware scheme to improve distributed caching in cellular networks via D2D underlay communications (Statistics, Optimization & Information Computing, 2024)
Underlay Device-to-Device (D2D) communications is a promising networking technology intended to boost thespectral efficiency of future cellular networks, including 5G and beyond. When used for distributed caching, where cellulardevices store popular files for direct exchange later with other devices away from the cellular infrastructure, the technologybears more fruits such as enhancing throughput, reducing latency and offloading the infrastructure. However, due to theirnon-orthogonality, underlay D2D communications can result in excessive interference to the cellular user. To avoid thisproblem, the present article proposes a scheme with two interference-reduction elements: a guard zone intended to allowD2D communications only for devices far enough from the base station (BS), and a pairing strategy intended to allow D2Dpairing for only devices that are close enough to each other. We assess the performance of the scheme using a stochasticgeometry (SG) model, through which we characterize the coverage probability of the cellular user. This probability is aprincipal indicator of maintaining the quality of service (QoS) of the cellular user and of enabling successful caching for theD2D user. We introduce in the process a novel empirical technique which, given a desired level of interference, identifiesan upper bound for the distance between two devices to be paired without exceeding that level. We finally validate theanalytical findings obtained from the model by intensive simulation to ensure the correctness of both the model and thescheme performance. A salient feature of the scheme is that it requires for its implementation no software or hardwaremodification in the device